The Role of Workplace Enviousness on Individual Productivity and Organizational Behavior - Qusay H. ‎Al-Salami; Mustafa J. Issa (Cihan University-Erbil Journal of Humanities and Social Sciences, 2023)
As a result of its negative consequences for college academics, workplace envy is one of the important areas to study and investigate its results. Thus, this study attempts to find out individuals’ productivity affected by envy in the workplace (CWBI) and organizational citizenship behavior directly benefi ts individuals (OCBI) in the context of Iraqi colleges. A survey was conducted among the lecturers at Baghdad University’s colleges in Iraq, with 182 lecturers representing a response rate of 50%. The researcher used two-step approach with partial least squares-structural equation modeling by Smart PLS to test the hypotheses. As anticipated, the research findings point that workplace envy positively influenced CWBI (accepting H1). Furthermore, results indicated that workplace envy negatively influenced OCBI (accepting H2). The results of this research have various implications for colleges in general and Iraqi colleges in particular. The scientific impact that the results of the present study will contribute to practitioners is demonstrated by highlighting the factors that lead to reducing CWBI and strengthening OCBI in colleges. To enhance the OCBI and minimize the CWBI in colleges, it is advised that the management should encourage academic cooperation and create a work environment suitable for the academics. This can be achieved by forming research teams to work on joint scientific projects and by allowing qualified academics to participate in teaching, supervising postgraduate students, and discussion committees. Providing positive organizational support can motivate the academics to perform better, exhibit responsible behavior, and become productive members of the college community.